2011
DOI: 10.1534/genetics.111.130724
|View full text |Cite
|
Sign up to set email alerts
|

The Rho1 GTPase Acts Together With a Vacuolar Glutathione S-Conjugate Transporter to Protect Yeast Cells From Oxidative Stress

Abstract: Maintenance of redox homeostasis is critical for the survival of all aerobic organisms. In the budding yeast Saccharomyces cerevisiae, as in other eukaryotes, reactive oxygen species (ROS) are generated during metabolism and upon exposure to environmental stresses. The abnormal production of ROS triggers defense mechanisms to avoid the deleterious consequence of ROS accumulation. Here, we show that the Rho1 GTPase is necessary to confer resistance to oxidants in budding yeast. Temperature-sensitive rho1 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…We found enhanced phosphorylation at a MAPK consensus site of Sod1, the cytosolic Cu-Zn superoxide dismutase. Of interest, another up-regulated protein in our analysis, the vacuolar glutathione S-conjugate transporter Ycf1, recently has been found to bind to the Pkc1 activator Rho1 upon induction of oxidative stress by peroxides (74). The identified Ycf1 Ser878 residue fits a putative Pkc1 target motif.…”
Section: Discussionmentioning
confidence: 85%
“…We found enhanced phosphorylation at a MAPK consensus site of Sod1, the cytosolic Cu-Zn superoxide dismutase. Of interest, another up-regulated protein in our analysis, the vacuolar glutathione S-conjugate transporter Ycf1, recently has been found to bind to the Pkc1 activator Rho1 upon induction of oxidative stress by peroxides (74). The identified Ycf1 Ser878 residue fits a putative Pkc1 target motif.…”
Section: Discussionmentioning
confidence: 85%
“…Rho GTPase Essential GTPase that is required for cell wall remodeling and resistance to oxidative stress Functions as a regulatory subunit for the glucan synthases Fks1 and Fks2 and also regulates Pkc1 and Mpk1-mediated cell wall integrity pathway Regulates formin activation and exocytosis Regulates actin ring assembly and cytokinesis Yamochi et al 1994;Drgonova et al 1996;Kohno et al 1996;Qadota et al 1996;Drgonova et al 1999;Guo et al 2001;Tolliday et al 2002;Dong et al 2003;Yoshida et al 2006;Yoshida et al 2009;Lee et al 2011 (continued) Cell wall synthesis Binds to regulatory subunit Rho1 Localizes to sites of polarized growth fks1D and fks2D are synthetically lethal Parent et al 1993;Douglas et al 1994;Inoue et al 1995;Mazur et al 1995;Drgonova et al 1996;Qadota et al 1996 Fks2 Catalytic subunit of 1,3-b-D-glucan synthase Effector of Rho1…”
Section: Rho1mentioning
confidence: 99%
“…It also interacts with the Rho1p nucleotide exchange factor, Tus1p (18). Others have found that Ycf1p physically interacts directly with Rho1p, a GTPase associated with actin dynamics (40). Because Rho1p (41), actin (42,43), and PI3P (3) play important roles in vacuole fusion, we examined the effect of deleting YCF1 and other ABCC transporters on vacuole fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Tus1p is the nucleotide exchange factor for Rho1p, a GTPase involved in actin remodeling and vacuole fusion (41,52). Moreover, Ycf1p directly interacts with Rho1p (40). Because actin remodeling is essential for vacuole fusion at different stages of the reaction, we can theorize that in the absence of Ycf1p, Rho1p might be inactive, resulting in a reduction in actin polymerization on vacuoles.…”
Section: Discussionmentioning
confidence: 99%